Self-sterilizing ormosils surfaces based on photo-synzthesized silver nanoparticles - Gonçalves, Lidiane Patrícia (2018)
Medical device-related infections represent a major healthcare complication, resulting in potential risksfor the patient. Antimicrobial materials comprise an attractive strategy against bacterial colonizationand biofilm proliferation. However, in most cases these materials are only bacteriostatic or bactericidal,and consequently they must be used in combination with other antimicrobials in order to reach theeradication condition (no viable microorganisms). In this study, a straightforward and robust antibac-terial coating based on Phosphotungstate Ormosil doped with core-shell (SiO2@TiO2) was developedusing sol-gel process, chemical tempering, and Ag nanoparticle photoassisted synthesis (POrs-CS-Ag).The coating was characterized by X-ray Fluorescence Spectroscopy (XRF), Field Emission ScanningElectron Microscopy (FE-SEM), Atomic Force Microscopy (AFM) and X-ray Photoelectron Microscopy(XPS). The silver free coating displays low antibacterial activity against Staphylococcus aureus and Pseu-domonas aeruginosa, in opposition to the silver loaded ones, which are able to completely eradicate thesestrains. Moreover, the antimicrobial activity of these substrates remains high until three reutilizationcycles, which make them a promising strategy to develop self-sterilizing materials, such as POrs-CS-Ag-impregnated fabric, POrs-CS-Ag coated indwelling metals and polymers, among other materials.